MENJADI GENERASI UNGGUL DAN BERKARAKTER UNTUK MENGGAPAI KESUKSESAN - Ngatipan Ngatipan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
The superior generation is a generation that has intelligence and good character within itself, always has a positive impact on oneself, others and creatures around their environment. Education that can give birth to a superior generation is education that can also strengthen the will so that everyone who knows moral goodness really wants to live according to the knowledge they have. The superior generation is the product or result of the habituation of character values ​​originating from spiritual intelligence. is the ability to